2013
DOI: 10.1037/a0028783
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and work-related correlates of job burnout in professional eating disorder treatment providers.

Abstract: Patients with eating disorders present unique challenges to treatment providers that may contribute to job burnout. This study examined demographic and work-related correlates of three primary components of burnout (i.e., emotional exhaustion, cynicism, and lack of personal accomplishment) in a sample of 296 professional eating disorder treatment providers. Participants completed the Maslach Burnout Inventory-Human Services Survey (MBI-HSS; Maslach, Jackson, & Leiter, 1996), demographics, and a questionnaire d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(80 citation statements)
references
References 75 publications
4
69
1
6
Order By: Relevance
“…Clinician experience seems to play an important role in predicting negative responses, with more experienced therapists reporting less negative emotional responses (Warren et al, 2013). We did not examine the influence of specific clinical experience in treating ED patients, and further research is needed to clarify the different impacts between general and specific clinical experience.…”
Section: Discussionmentioning
confidence: 92%
“…Clinician experience seems to play an important role in predicting negative responses, with more experienced therapists reporting less negative emotional responses (Warren et al, 2013). We did not examine the influence of specific clinical experience in treating ED patients, and further research is needed to clarify the different impacts between general and specific clinical experience.…”
Section: Discussionmentioning
confidence: 92%
“…All participants found their work professionally rewarding. This is consistent with previous research that has also found high levels of professional satisfaction in individuals working in eating disorder services (Colli et al ., ; Davey et al ., ; Warren et al ., , ). However, participants identified specific challenges related to working with individuals with eating disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Five of these questions related to occupational therapy-specific practice in eating disorders and eight were related to challenges associated with working with individuals with eating disorders. These questions were developed from literature surrounding professional identity for occupational therapists in mental health (e.g., Ashby et al, 2013;Hayes et al, 2008;Scanlan, Still, Stewart & Croaker, 2010) and job challenges for staff working in eating disorder services (Davey et al, 2014;Warren et al, 2012Warren et al, , 2013. The specific wording of the questions is outlined in Table 2 in the results section.…”
Section: Job Challengesmentioning
confidence: 99%
See 2 more Smart Citations